Implementation of multiple criteria decision analysis approaches in the supplier selection process: a case study - Kisly, Dmitry (2016)
Supplier evaluation and selection is recognized as a multiple criteria problem. Having considerable economic impact and influencing a competitive position of a buyer, supplier selection has been modelled by different multiple criteria decision analysis approaches. This case study focuses on the reported "relevance gap" between theoretical approaches to the supplier selection problem and practice. The research was conducted in a textile group, addressing a typical buying situation of a main raw material. The decision process was structured with weighted score, AHP and goal programming models. Three models elaborated have led to the very similar output, recognized as realistic and consistent by the decision makers. Acquired skills of multiple criteria decision analysis were considered as beneficial for supplier selection decisions.